Relationship between Communication Barriers and Stress in Parents with Deaf Children in Elementary Level Special Needs School in Pekanbaru - Damayanti, Indah (The Center for Disability Studies and Services Brawijaya University, 2019)
Constraints in communication are generally experienced by parents with deaf children, especially in elementary school age. The inability of children to hear and the lack of vocabulary mastered by children causes difficulties in understanding and conveying messages between parents and children. This causes the need for parents to convey and receive messages from children not achieved perfectly and cause stress. This study aims to determine the relationship between barriers to communication with stress in parents who have deaf children at primary school level at SLBN (state special needs school) Pembina Pekanbaru. The method in this study uses a quantitative approach with correlational research design. This research is a population research, with the subject of the research are all parents who have deaf children at the elementary school level in the SLBN Pembina Pekanbaru, total 42 people. The data of this study were obtained using a scale of communication barriers revealed by researchers from the theory described by Fajar (2009) regarding the barriers to communication and stress scale revealed by researchers from the theory of Sarafino (1997) regarding stress and symptoms. The results of data analysis using the Product Moment correlation technique from Pearson through the help of the SPSS 24.0 for windows program showed a value of r = 0.819 with a significant value p = 0.00, meaning there is a positive relationship between communication barriers to stress in parents who have deaf children at primary school level in the SLBN Pembina Pekanbaru.